Toxoplasma gondii ... - Scherrer, Patrick; Ryser-Degiorgis, Marie-Pierre; Marti, Iris A.; St; Borel, ephanie; Frey, Caroline F.; Mueller, Norbert; Ruetten, Maja; Basso, Walter (Zenodo, 2023)
4.2. Epidemiology of T. gondii in the wild Transmission of T. gondii can occur in a wide variety of ways, including oral (carnivorism), faeco-oral and transplacental transmission. In felids, ingestion of tissue cysts from intermediate hosts is the most efficient route of transmission (Dubey, 2006). The diet of the Eurasian lynx in western and central Europe comprises mainly larger ungulates (Breitenmoser and Breitenmoser-Würsten, 2008). In Switzerland, roe deer (Capreolus c. capreolus) are the undisputed main prey, followed by chamois (Rupicapra r. rupicapra) and, to a minor extent, foxes (Vulpes vulpes) (Molinari-Jobin et al., 2007). Although no studies have been carried out in Switzerland on T. gondii infections on the main lynx prey yet, its occurrence in roe deer and chamois was demonstrated in Italy and France by high seroprevalences of 13–43.7% and 3.8–16.8%, respectively (Gaffuri et al., 2006; Gotteland et al., 2014; Crotta et al., 2022). Similar numbers might be expected in Switzerland. Another ... : Published as part of Scherrer, Patrick, Ryser-Degiorgis, Marie-Pierre, Marti, Iris A., St, Borel, ephanie, Frey, Caroline F., Mueller, Norbert, Ruetten, Maja & Basso, Walter, 2023, Exploring the epidemiological role of the Eurasian lynx (Lynx lynx) in the life cycle of Toxoplasma gondii, pp. 1-10 in International Journal for Parasitology: Parasites and Wildlife 21 on page 7, DOI: 10.1016/j.ijppaw.2023.03.005, http://zenodo.org/record/10668262 ...